Macroeconomic Impacts of ALMP on the Matching Process in West Germany - Reinhard Hujer; Christopher Zeiss (Institute for the Study of Labor (IZA), 2003)
This paper investigates the macroeconomic effects of job creation schemes and vocational training on the matching processes in West Germany. The empirical analysis is based on regional data for local employment office districts for the period from 1999 to 2003. The empirical model relies on a dynamic version of a matching function augmented by ALMP. In order to obtain consistent estimates in the presence of a dynamic panel data model, a firstdifferences GMM estimator and a transformed maximum likelihood estimator are applied. Furthermore the paper considers the endogeneity problem of the policy measures. The results obtained from our estimates indicate that vocational training does not significantly affect the matching process and that job creation schemes have a negative effect.
Keywords: C23; J68; J64; H43; E24; 330; Active Labour Market Policy; dynamic panel data model; matching function; search models; Arbeitsmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Ökonometrisches Makromodell; Panel; Arbeitsmarkt; Matching; Schätzung; Deutschland